Demographic and developmental patterns in telomere length across adolescence. (1st October 2020) - Gaydosh, Lauren; Mitchell, Colter; Notterman, Daniel; Schneper, Lisa; Brooks-Gunn, Jeanne; Wagner, Brandon; Koss, Kalsea; McLanahan, Sara
ABSTRACT: Telomere length is often used in studies of adults as a biomarker of cellular aging and an indicator of stress exposure. However, we know little about how telomeres change over time, particularly over the course of the important developmental period of adolescence. We use data on telomere length collected at two points in time spanning adolescence (Years 9 and 15) from the Fragile Families and Child Wellbeing Study to examine longitudinal patterns ( n = 1, 654) in telomere length. We find a quantitatively small but significant average lengthening in telomere length across adolescence and little evidence of associations between telomere length and pubertal development.